2019
DOI: 10.1007/s40519-019-00794-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between food addiction and patterns of disordered eating with exercise dependence: in amateur endurance athletes

Abstract: Purpose Examine the prevalence and potential relationships among food addiction (FA)-as measured by Yale Food Addiction Scale 2.0 (YFAS 2.0), eating disorders (ED)-as measured by Eating Disorder Diagnostic Scale (EDDS)-and exercise dependence (EXD)-as measured by Questionnaire to Diagnose Exercise Dependence in Endurance Sports (FESA), for the first time worldwide, in amateur endurance athletes. Methods A total of 1022 German-speaking endurance athletes (44% male, Ø 36 years, Ø BMI 23 kg/m 2) replied to an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
(99 reference statements)
2
12
0
1
Order By: Relevance
“…It would be necessary to objectively examine (by means of accelerometers) the amount of physical activity performed. Furthermore, it would be interesting to explore whether there is any relationship with addictive behaviors towards sport, as it has been observed that in athletes the conjunction of both addictions exists [ 36 ]. Young university students may be trying to compensate for their addiction to food by over-exercising, which in turn may lead to a dependence on exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It would be necessary to objectively examine (by means of accelerometers) the amount of physical activity performed. Furthermore, it would be interesting to explore whether there is any relationship with addictive behaviors towards sport, as it has been observed that in athletes the conjunction of both addictions exists [ 36 ]. Young university students may be trying to compensate for their addiction to food by over-exercising, which in turn may lead to a dependence on exercise.…”
Section: Discussionmentioning
confidence: 99%
“…FA, in obese patients or university students, was consistently associated with self-report and other measures of impulsivity; associations with reward sensitivity were inconsistent, depending on the questionnaires used [ 34 ]. At last, FA prevalence was generally increased in patients with other chemical or behavioral addictions as compared with non-clinical samples [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, eating is necessary for survival and drug use is not; eating is intrinsically rewarding and reinforcing, and food consumption is well known to naturally activate the brain reward system. Most other authors, however, considered FA to fit better with SUD [ 4 , 7 , 13 , 37 , 41 , 42 ]. Two properties of food could participate in mediating liking, wanting, or craving: hedonic taste and metabolic shifts following ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…This can generate withdrawal syndrome, anxiety, and irritability when training is missed, giving rise to what is called negative running addiction (NRA). NRA is manifested to a greater degree in long-distance runners [6] and competitive athletes due to their greater commitment to training in order to achieve the desired records [6,7]. Initially, NRA was associated mainly with men, but in recent years, studies have found that both sexes experience it [5,6].…”
Section: Introduction 1exercise Dependence In Competitive Athletesmentioning
confidence: 99%
“…NRA is manifested to a greater degree in long-distance runners [6] and competitive athletes due to their greater commitment to training in order to achieve the desired records [6,7]. Initially, NRA was associated mainly with men, but in recent years, studies have found that both sexes experience it [5,6].…”
Section: Introduction 1exercise Dependence In Competitive Athletesmentioning
confidence: 99%